Development of Learning Instruments Based on The Problem Based Learning Model to Facilitate Students' Mathematical Problem Solving Skill on Curved 3D Shapes - Saputra, Heru; Maimunah; Yuanita, Putri (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
The aim of this study was to develop educational materials, including syllabi, lesson plans, and worksheets, utilizing a problem-based learning approach to enhance the mathematical problem-solving abilities of ninth-grade junior high school students in dealing with curved side 3D space problems. This research falls under the category of development research (R&D) and employs the 4-D method, which involves defining, designing, developing, and disseminating. The outcome of the study is the creation of valid and practical learning materials, validated by experts with scores of 3.88 for the syllabus, 3.84 for the lesson plans, and 3.77 for the worksheets, meeting the criteria for high validity. Additionally, the practicality scores obtained from small and large group trials were 3.64 and 3.61, respectively, indicating a high level of practicality. In conclusion, the mathematics learning materials developed based on the problem-based learning model for the topic of curved 3D shapes effectively support the enhancement of students' mathematical problem-solving skills at the ninth-grade level, meeting both validity and practicality criteria.